The Causes of Price Inflexibility - Backman, Jules (Quarterly Journal of Economics, 1940)
Classification of factors determining price rigidities, 474. — Characteristics of the product, 476. — Law or administrative decree, 481. — Concentration of control, 482. — Marketing techniques, 484. — Habits and customs, 486. — Contractual arrangements, 486. — Structure of the market, 487. — Conclusions, 488.